Estudo da “NBR 15575 edificações habitacionais – desempenho” e sua influência no cenário da construção civil local. - Souza, Barbara Pereira de (Universidade Federal Rural do Semi-Árido, 2019)
The ABNT NBR 15575, the performance standard for residential buildings published in 2013, establishes parameters for project specification and design, determining minimum performance requirements for buildings in order to improve the quality of buildings, meeting the requirements of the consumer. This paper aims to understand how the NBR 15.575 - Housing Buildings - Performance, contributes to the evolution in construction and its importance to the area. To fulfill the objective of the work, besides the exploratory research along with the bibliographic survey, a questionnaire was applied that aimed to know the perception of civil engineers, representatives of construction companies in the city of Mossoró, regarding the importance and impacts generated by the Performance Standard, and how it has been applied today in the state of Rio Grande do Norte. The results indicate that, in general, most of the interviewed Engineers consider the use of the Performance Standard advantageous and important for the civil construction despite the increase in the cost, because the described requirements offer a better quality building and, consequently, a bigger one. lifetime, as well as establishing a better division of tasks for each constituent of the work, from materials supplier, designer to performer and clarifying the importance of maintenance on buildings.
Monografia
Keywords: NBR 15575; Desempenho; Manutenção; Construção Civil.; Vida útil; Edificações; Performance; Maintenance; Lifespan; Construction.; Buildings; ENGENHARIAS::ENGENHARIA CIVIL